PENGUATAN RANTAI STOK AGRIBISNIS RUMPUT LAUT DI PERAIRAN PESISIR KALEDUPA - Akhmad Mansyur (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2014)
This research aimed to strengthening agribusiness seaweed stock chain in Kaledupa Coastal Waters. clasification of region function, optimum production rotation, comodity price and region collateral value incentive, optimum phycoculturer distribution and business grops break-even point used to analysis. As a result, there are two classifications function region is to support the seedlings and supporting carrageenan. Respectively, have the optimum harvest periods 28 and 42 days per production. At IDR 216 and 362 per unit product (kg) cost, comodity floor price can be achieve IDR 307 and 1.584 per kg, Upper price achieve IDR 2.827 and 4.732 per kg. Each region collateral price is IDR 16.985.477/ha/years and 32.610466/ha/years. Optimum phycoculturer distribution at each region can be achieve 124 and 148 labor with a 5 percent increase each collateral realization. Optimum members distribution in grops to capital acces is 8 families per grops of KS and KSS. Access control aspects is the break-even sales effort of 1,543 kg at a base price of IDR 307/kg of KS and 1,794 kg at a base price of IDR 1,584/kg of KSS. Thus, region function specialization, region collateral value aplication and giving management knit coastal water sertificate based on distribution and optimum groping phycoculturer can be used as strengthening stock chain for seaweeds agribusiness in Kaledupa coastal waters.